Semilocal connectedness of product spaces and s-continuity of maps - Janina Ewert (International Journal of Mathematics and Mathematical Sciences)
We consider the problem of the transfer of semilocal connectedness from factors to the product space and vice versa. Some sufficient conditions are given under which the product of semilocally connected spaces is semilocally connected. Obtained theorems are not invertible, suitable examples are given.